A Study of The Fish Supply Chain at The Paotere Fishing Port of Makassar City - Kahar, Karmila; Amiluddin, Amiluddin; Tahang, Hamzah (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2023)
This study aims to determine (1) the flow of information and finance, (2) the main problems that occur in supply chain activities at PPI Paotere, and (3) supply chain models at PPI Paotere. This research was conducted in March 2021 at PPI Paotere, Makassar City. The type of research used is survey research using a quantitative approach. The sampling method used cluster sampling and the determination of the number of samples with the Slovin formula, so that the number of samples as many as 43 people. The data analysis used in this study is a quantitative and qualitative descriptive analysis. The results showed that in terms of information flow, pelagic and demersal fish sources of information mostly came from groups of fishermen, courtiers and even other traders. Financial flow with a system of mutual trust that has been built and maintained for a long time because the average supplier and trader have been subscribing for years. The flow of goods starts from the source of goods originating from fishermen who are obtained from nearby islands until they finally arrive to consumers and industry. There are various problems experienced by market players at the Paotere fishing port, including the timeliness of auctions, checking the number and types of fish and cooperative services at the Paotere fishing port. The supply chain model for pelagic and demersal fish in the Paotere fishing port is divided into two, namely for export needs and local consumers. The supply chain model for local consumer needs consists of groups of fishermen, courtiers, traders and consumers while for export needs consists of groups of fishermen, retainers, UPI, companies then exported.